Implementasi Kebijakan Penataan Ruang Terbuka Hijau di Kabupaten Purbalingga - Riyanto, Refiana Adista; Subekti, Rahayu (Universitas Pendidikan Ganesha, 2025)
This study aims to find out how the implementation of green open space arrangement policies in Purbalingga based on the Regional Regulation of the Purbalingga Regency number 10 of 2020 concerning the Purbalingga Regency Spatial Plan for 2011-2031 and its obstacles. This study is a empirical or sociological legal research with the nature is descriptive. This study uses a qualitative approach with primary data sources and secondary data sources as its data sources. The data collection technique that used in this study is through interviews, document studies, and observation. The results of this study indicate that the total percentage of green open space in Purbalingga is still very far from the proportional number. In 2021 Purbalingga only reach the amount of 5,689% from 30% as the proportional number for green open space. In achieving this proportional amount, the implementation of the green open space arrangement policy itself has not been implemented optimally. This is due to various kinds of obstacles faced such as limited land and lack of public awareness of the important role of green open space.